Heme Drives Oxidative Stress-Associated Cell Death in Human Neutrophils Infected with Leishmania infantum - Quintela-Carvalho, Graziele; Luz, Nívea F.; Celes, Fabiana S.; Zanette, Dalila L.; Andrade, Daniela; Menezes, Diego; Tavares, Natália M.; Brodskyn, Claudia I.; Prates, Deboraci B.; Gonçalves, Marilda S.; de Oliveira, Camila I.; Almeida, Roque P.; et al. (Frontiers in Immunology, 2017)
Free heme is an inflammatory molecule capable of inducing migration and activation of neutrophils. Here, we examine the heme-driven oxidative stress-associated cell death mechanisms in human neutrophils infected with Leishmania infantum, an etiologic agent of Visceral Leishmaniasis (VL). We first performed exploratory analyses in a population of well characterized treatment-naïve VL patients as well as uninfected controls, who were part of previously reported studies. We noted a positive correlation between serum concentrations of heme with heme oxygenase-1 (HO-1) and lactate deydrogenase, as well as, a negative correlation between heme values and peripheral blood neutrophils counts. Moreover, in vitro infection with L. infantum in the presence of heme enhanced parasite burden in neutrophils, while increasing the production of reactive oxygen species and release of neutrophilic enzymes. Additional experiments demonstrated that treatment of infected neutrophils with ferrous iron (Fe+2), a key component of the heme molecule, resulted in increased parasite survival without affecting neutrophil activation status. Furthermore, stimulation of infected neutrophils with heme triggered substantial increases in HO-1 mRNA expression as well as in superoxide dismutase-1 enzymatic activity. Heme, but not Fe+2, induced oxidative stress-associated cell death. These findings indicate that heme promotes intracellular L. infantum survival via activation of neutrophil function and oxidative stress. This study opens new perspectives for the understanding of immunopathogenic mechanisms involving neutrophils in VL.